PERAN MANAJEMEN PERPUSTAKAAN DALAM MEMBERIKAN PELAYANAN KEPADA MASYARAKAT DIKABUPATEN BULELENG - Kadek Duwika (Universitas Panji Sakti, 2023)
This article is the result of an exploration of the literature that supports the role of library management in improving quality with various cultural backgrounds. The method of writing analysis from the literature found by the author with a qualitative approach. The exploration results show that one of the supporting facilities for the Regional Archives and Libraries Service of Buleleng Regency is the role that exists in the library. The provision of a library also supports the implementation of development in Buleleng Regency. The library is a dynamic space that can build works of human civilization. The progress of culture and civilization of a nation cannot be separated from the progress of the available libraries. The progress and decline of a nation lies in the library it has. Like the life of the library is the heart of a life.